New ways of working and the physical environment to improve employee engagement - Duque, L.; Costa, R.; Dias, Á.; Pereira, L.; Santos, J.; António, N. (Sustainability, 2020)
Employee engagement is becoming an increasingly essential factor in organizational competitiveness. Although employee engagement is an extensively researched topic, the roles of new ways of working and physical environment factors are still under exploited. As such, this study examines the relationship between physical environment factors, the dimensions that integrate new ways of working, and employee engagement. Survey data with 126 respondents are analyzed using structural equation modeling. The findings indicate a positive significant relationship between the physical environment factors and work engagement. Furthermore, this relation is mediated by four facets regarding new ways of working. The results also indicate that, for the group where facilities were not modified, the new ways of working are a stronger predictor of work engagement when compared with the group where facilities were modified. These findings extend existing knowledge on the antecedents of employee engagement, namely physical environment factors and new ways of working. Another important contribution is related to the mediating role of several facets of new ways of working in the relationship between physical environmental factors and employee engagement.